Endangered daughters : discrimination and development in Asia - Croll, Elisabeth, 1944-2007 (Health, risk and society., 2000)
"This book asks the controversial question of why millions of girls do not appear to be surviving to adulthood in contemporary Asia. In the first major study available of this sensitive and emotive issue, Elisabeth Croll investigates the extent of discrimination against female children in Asia and shifts the focus of attention firmly from son preference to daughter discrimination." "The book paints a vivid picture of daughter discrimination across Asia today, from excessive child mortality to the withholding of health care and education on the basis of gender. It argues that daughters still cannot substitute for sons and that the increasing availability of sex-identification technologies will serve only to supplement older forms of infanticide and neglect. Startlingly, it reveals that, in China, India and across East and South Asia, daughter discrimination is actually on the increase despite rising economic development, declining fertility and the generally improved status of women." "This compelling account of a phenomenon still hidden and unacknowledged across the world is essential reading for all those interested in gender and children in contemporary society."--Jacket